2016
DOI: 10.4103/1995-705x.182642
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic multicentric right atrial and right ventricular myxoma presenting as acute pulmonary thromboembolism

Abstract: Multicentric cardiac myxoma is a rare syndrome; usually it is familial. We report a rare case of sporadic right atrium (RA) and right ventricle (RV) myxoma in a 26-year-old female presenting to our hospital for the evaluation of sudden onset of dyspnea and left precordial pain attributed to the embolization of degenerating tumor fragments to the pulmonary artery (PA). The exact incidence of sporadic multicentric RA and RV myxoma presenting as acute pulmonary embolism is unknown as multicentric RA and RV myxoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…The oldest case was published in 1971 [14], and the most recent one, apart from ours, in 2016 [4]. Singh el al.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The oldest case was published in 1971 [14], and the most recent one, apart from ours, in 2016 [4]. Singh el al.…”
Section: Discussionmentioning
confidence: 87%
“…reported two cases of cardiac masses in his article, however only one of them was confirmed as a myxoma and included in our review [10]. Eight of the 11 cases were reported in English language [4–8, 10, 12, 13]. Urina Triana et al reported their case in Spanish language.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations